Strategi Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan di MTS Al-Munawaroh - Khoirul Muttaqin (Jurnal Ilmu Pendidikan dan Sosial, 2025)
Education is one of the important factors in the progress of a nation, and improving the quality of education is one of the main priorities of the Indonesian government. To achieve these goals, school principals have a strategic role in managing and developing educational resources. This study aims to identify and analyze the strategies implemented by principals at MTs Al-Munawaroh in improving the quality of education. A qualitative approach was used to explore various aspects related to practices, policies and challenges faced by principals in an effort to improve the quality of education. Primary data sources are principals and teachers. Secondary data from relevant books and journals. The results showed that principals at MTs Al-Munawaroh implemented several important strategies, including improving teachers' pedagogical competence through regular training and workshops, as well as using innovative and technology-based learning methods. Principals also implement regular learning supervision to ensure that the learning process runs in accordance with established standards. In addition, the involvement of parents and the community in school activities is an important strategy in supporting the development of education quality, which is organized through the School Council. Improving facilities and infrastructure is also a major focus in supporting the quality of learning. With these strategies, MTs Al-Munawaroh has succeeded in creating a conducive and quality educational environment. This research is expected to provide insight for other schools that want to improve the quality of education through a similar approach.